Idiot : life stories from the creator of help helen smash - Clery, Laura (Gallery Books, 2019)
"From YouTube star and Facebook Video sensation Laura Clery comes a collection of comedic essays in the vein of We Are Never Meeting in Real Life by Samantha Irby and You'll Grow Out of It by Jessi Klein. Laura Clery makes a living by sharing inappropriate comedy sketches with millions of strangers on the Internet. She writes songs about her anatomy, talks trash about her one-eyed rescue pug, and sexually harasses her husband, Stephen. And it pays the bills! Now, in her first-ever book, Laura recounts how she went from being a dangerously impulsive, broke, unemployable, suicidal, cocaine-addicted narcissist, crippled by fear and hopping from one toxic romance to the next...to a more-happy-than-not, somewhat rational, meditating, vegan yogi with good credit, a great marriage, a fantastic career, and four unfortunate-looking rescue animals. Still, above all, Laura remains an amazingly talented, adorable, and vulnerable, self-described...Idiot. With her signature brand of offbeat, no-holds-barred humor, Idiot introduces you to a wildly original-and undeniably relatable-new voice"--